특수교육 대상 아동들의 사회성 기술 향상을 위한 스마트 콘텐츠 개발 - 한동욱(Dong-Wook Han); 강민채(Min-Chae Kang) (한국콘텐츠학회 논문지, 14(12), 2014)
본 연구는 특수교육 대상 아동들의 사회성 기술 향상을 위한 앱을 개발하고 개발한 콘텐츠의 사용성의 차이가 있는지를 검증한 논문이다. 특수교사 및 장애 아동의 부모, 장애아동 행동관찰 등 다양한 사용자와의 인터뷰를 통해 마트이용하기 앱을 개발하였다. 교수설계와 스마트 콘텐츠 설계원리를 기준으로 시각적인 자료 사진, 청각적 안내, 시간안내 등 다감각적으로 학습할 수 있도록 스마트 콘텐츠 교육프로그램을 구성하였다. 앱의 사용성에 대한 설문 조사를 수행하기 위해 총 34명의 특수 교육 기관의 교사와 장애 아동을 둔 부모를 두 집단으로 나누었다. 그룹 1은 실제 사진과 동영상을 활용한 프레젠테이션 중심의 멀티미디어 교수 자료를 제작하여 마트 이용하기를 교육하였고, 그룹 2는 개발한 앱을 활용하여 교육하였다. 분석결과 앱을 활용한 마트 이용하기가 프레젠테이션 기반의 교육보다 효과성, 효율성, 만족도 세 가지 관점에서 사용성이 더 높은 것으로 나타났다 The purpose of this study is to develop a smart application to enhance social skills of students with disability and to verify the usability of the developed application. The application to teach to shop was developed through interviews with special education teachers and parents of disabled children and observation of behaviors of students with disability. We developed a smart contents education program to support multi-sensuous learning which contains visual photographs, auditive guidance, time keeping, and etc. based on the instructional design of smart contents. Teachers in special education and parents of disabled students, totally 34 people, were divided into two groups to survey usability of developed application. Group 1 used multi-media materials mainly containing slideshows to teach students while group 2 used the smart phone application developed by the researcher. KCI Citation Count: 6